2018
DOI: 10.3389/fpls.2018.00251
|View full text |Cite
|
Sign up to set email alerts
|

Antagonistic Regulation of ABA and GA in Metabolism and Signaling Pathways

Abstract: The phytohormones gibberellic acid (GA) and abscisic acid (ABA) are widely recognized as essential endogenous regulators that mostly play antagonistic roles in plant developmental processes and environmental responses. A variety of both internal and external cues oppositely regulate GA and ABA biosynthesis and catabolism, which directly and indirectly affect their signaling pathways and subsequent responses. Recent discoveries have revealed direct molecular links between GA- and ABA-signaling components, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
114
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(123 citation statements)
references
References 63 publications
(70 reference statements)
6
114
1
2
Order By: Relevance
“…Some researchers suggested that the competition between flower buds and food for fruit and assimilates is responsible for this phenomenon (Cetinkaya, 2004;Ulger et al, 2004;Baninasab et al, 2006;Mirsoleimani et al, 2014) while others stated that unbalanced nutrition was not the main cause of the inhibition of flower bud formation, and more attention should be paid to the hypothesis of PGRs (Baktır et al, 2004;Gomez-Jimenez et al, 2010;Vemmos, 2010;Gundesli et al, 2019). In higher plants, ABA and GA antagonistically regulate various physiological growth periods, including seed dormancy, seed germination, root growth, shoot elongation, leaf development, flowering, flower bud formation, abscission, and fruit development, as well as biotic and abiotic stresses (Vanstraelen and Benková, 2012;Liu and Hou, 2018). ABA was first isolated from the mature flowers of cotton, rose, peas, and fruit as an abscission accelerator (Lui and Carns 1961;Mayak et al, 1972;Ehuwens and Schwabe, 1975).…”
Section: Discussionmentioning
confidence: 99%
“…Some researchers suggested that the competition between flower buds and food for fruit and assimilates is responsible for this phenomenon (Cetinkaya, 2004;Ulger et al, 2004;Baninasab et al, 2006;Mirsoleimani et al, 2014) while others stated that unbalanced nutrition was not the main cause of the inhibition of flower bud formation, and more attention should be paid to the hypothesis of PGRs (Baktır et al, 2004;Gomez-Jimenez et al, 2010;Vemmos, 2010;Gundesli et al, 2019). In higher plants, ABA and GA antagonistically regulate various physiological growth periods, including seed dormancy, seed germination, root growth, shoot elongation, leaf development, flowering, flower bud formation, abscission, and fruit development, as well as biotic and abiotic stresses (Vanstraelen and Benková, 2012;Liu and Hou, 2018). ABA was first isolated from the mature flowers of cotton, rose, peas, and fruit as an abscission accelerator (Lui and Carns 1961;Mayak et al, 1972;Ehuwens and Schwabe, 1975).…”
Section: Discussionmentioning
confidence: 99%
“…Phytohormones play key and distinct roles throughout the lifecycle, including seed dormancy, germination, and abiotic stress responses (Liu et al, ; Liu & Hou, ; Shu et al, ; Shu, Liu, Xie, & He, ; Shu, Zhou, Cheng, Luo, & Yang, ). It is widely recognized that ABA and GAs mediate seed dormancy and germination antagonistically (El‐Maarouf‐Bouteau & Bailly, ; Jeevan Kumar et al, ; Shu et al, ; Shu, Zhou, & Yang, ).…”
Section: Physiological and Genetic Factors Are Involved In Seed Longementioning
confidence: 99%
“…However, there is a large 2 body of work using percent germination as a measure of seed dormancy. A number of quantitative In-depth molecular studies have shown that the decision to germinate is controlled by the balance 9 between two hormones, gibberellic acid (GA), which promotes germination, and abscisic acid (ABA), 10 which represses it (Liu and Hou, 2018). These hormones function in a mutually antagonistic manner 11 by each inhibiting the synthesis and promoting the degradation of the other (Liu and Hou, 2018;12 Piskurewicz et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…A number of quantitative In-depth molecular studies have shown that the decision to germinate is controlled by the balance 9 between two hormones, gibberellic acid (GA), which promotes germination, and abscisic acid (ABA), 10 which represses it (Liu and Hou, 2018). These hormones function in a mutually antagonistic manner 11 by each inhibiting the synthesis and promoting the degradation of the other (Liu and Hou, 2018;12 Piskurewicz et al, 2008). Additionally, the two hormones have opposing effects on downstream 13 transcriptional regulators that control the balance between dormancy and germination (Liu et al, 14 2016; Piskurewicz et al, 2008;Shu et al, 2013).…”
Section: Introductionmentioning
confidence: 99%